Experimental and numerical evaluation of semi‐circular bending specimen for mixed mode I/III and pure mode III fracture tests. Issue 4 (26th January 2022) - Bakhshizadeh, Majid; Pirmohammad, Sadjad
Abstract: This paper suggests a simple loading configuration for conducting the SCB (semi‐circular bend) tests on brittle materials to produce mixed mode I/III loadings. In the suggested test setup, the SCB specimen containing an inclined crack is loaded using a conventional three‐point bending fixture, but the bottom supports touches nearly half of the specimen thickness rather than the entire thickness. It is found that various mixed mode I/III loadings can be provided by rotating the crack, and especially the SCB specimen experiences pure mode III when the crack angle is set to be 90°. Different values of the crack length, span and crack angle are then considered in the numerical analyses to further study the proposed SCB test setup. Finally, several experiments are successfully conducted on the rock samples under various mixed mode I/III and pure mode III loadings to evaluate the SCB test setup in practical point of view. Research highlights: A simple loading configuration is suggested for conducting the SCB tests. Mixed mode I/III and pure mode III tests can be performed using the SCB specimen. Effects of crack length, span and crack angle in the SCB tests are numerically explored. Mode III has a negative effect on the fracture resistance of rock materials.